Palm Oil 2018
DOI: 10.5772/intechopen.74863
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Oil Palm Wastes Charcoal Briquettes for Coal Replacement

Abstract: This study is aimed at investigating the potentials of oil palm wastes as an alternative to fossil fuels (coal) for domestic heat generation via briquettes (solid fuels) production. In this study oil palm wastes such as empty fruit bunches (EFB), mesocarp fiber (MF) and palm kernel shell (PKS) were pyrolyzed at temperatures of 400°C for 120 min and a heating rate of 10°C min −1. The biochar and bio-oil obtained were blended in the ratio of 60:40 weight percentages and compressed at a constant pressure of 400 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The observed relationship is explainable as the CEV decreases with the decrease in carbon content. These findings validate previous research on the energy generated by biomass fuels in which a high calorific value was acquired with an increase in C and H values [49,55].…”
Section: Biodegradation Studysupporting
confidence: 91%
See 1 more Smart Citation
“…The observed relationship is explainable as the CEV decreases with the decrease in carbon content. These findings validate previous research on the energy generated by biomass fuels in which a high calorific value was acquired with an increase in C and H values [49,55].…”
Section: Biodegradation Studysupporting
confidence: 91%
“…Asamoah et al (2016) reported that productive and highquality fuel pellets and briquettes depend on low MC, volatile matter, and ash content with high fixed carbon content [48]. High MC presence in biomass fuel will reduce the stability and density of the pellets and briquettes [49]. Low MC will produce high-quality fuel pellets and briquettes.…”
Section: Biodegradation Studymentioning
confidence: 99%
“…However, the percentage of biochar and pyrolytic liquid oil contributed mainly to the percentage of lignin, cellulose, and hemicellulose contents in the biomass feedstock. According to Safana et al [57] and Lee et al [97], the percentage of char yield is quite prominent in feedstock which contains a higher amount of lignin as compared to the cellulose and hemicellulose content, and it is vice-versa for a higher yield of pyrolytic liquid, which is proven by Sukiran et al [115]. Their experiment reported that OPEFB has the highest yield of pyrolytic oil (47 wt.%), and OPKS has the highest yield of char (55 wt.%) in comparison to other palm oil biomasses [115].…”
Section: The Production Of Liquid Biofuelmentioning
confidence: 99%
“…Charcoal briquettes, often overlooked, emerge as a significant renewable energy source (Safana et al 2018). Offering a sustainable alternative to natural forest-derived charcoal, these briquettes aid in conservation efforts and help reduce deforestation (Otieno and Otieno 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Palmyra (Chumsang and Upan 2014) and oil palm shells (Safana et al 2018) are recognized as abundant agro-wastes in local communities such as Thailand, with its 1.6 billion square meters of oil palm agricultural area in 2021 (Yaseen et al 2023). However, there are limited sources detailing the exact agricultural areas of palmyra palm.…”
Section: Introductionmentioning
confidence: 99%